2018
DOI: 10.2298/ijgi1801101m
|View full text |Cite
|
Sign up to set email alerts
|

Application of sustainable development principles in hotel business

Abstract: Tourism development, if not sustainable, could threat and affect the environment as an object of tourists' interest. Accordingly, hotels as a type of tourism organizations within a destination, are trying to involve sustainable business activities in their operations in order to protect the environment. In hotels within developed countries, sustainable activities are already implemented in the business and they are in the balance with the environment. However, implementation of these activities within societie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Sustainable tourism is a tourism concept that has an impact on the environment, social, culture and economy for the present and the future, both for local communities and tourists (Akinci et al 2018;Mijatov et al 2018). Furthermore, after the pandemic, it is estimated that there will be new normal conditions or new trends in traveling through sustainable tourism.…”
Section: Principles Of Sustainable Tourismmentioning
confidence: 99%
“…Sustainable tourism is a tourism concept that has an impact on the environment, social, culture and economy for the present and the future, both for local communities and tourists (Akinci et al 2018;Mijatov et al 2018). Furthermore, after the pandemic, it is estimated that there will be new normal conditions or new trends in traveling through sustainable tourism.…”
Section: Principles Of Sustainable Tourismmentioning
confidence: 99%
“…In addition, the development of urban tourism has been greatly contributed by the improvement of air travel and low-cost lines, as well as the emergence of new global hotel brands such as the Crowne Plaza, Holiday Inn, Radisson Blu, Mariott, Falkensteiner, Luxury Collection-Starwood in Belgrade and Sheraton in Novi Sad. Dynamic development is especially emphasized in the offer of different accommodation facilities, primarily four-star hotels, as well as the reconstruction and adaptation of a number of hotel facilities owned by local companies (Mijatov et al, 2018).…”
Section: Study Areamentioning
confidence: 99%
“…In the competitive environment of Serbia, when it comes to hotel offer of individual destinations and cities, employee satisfaction and desire to commit themselves to the organization is very important along with the intention to remain there. If managers want their organization to be competitive, then the focus must be on human motives Mijatov, Pantelić, Dragin, Perić, & Marković, 2018), including spiritual and physical development of their abilities. Blešić, Popov-Raljić, and Romelić (2007) reported that employees in the hotel industry should have adequate knowledge and skills that will provide both expected and additional quality services.…”
Section: Introductionmentioning
confidence: 99%
“…Serbian traditional cuisine contains a myriad of flavors and smells, mixture of tastes as a result of influences of various nations who live in this region. This fusion of different influences represents unique hedonistic culinary experiences that can only be enjoyed in Serbia, especially as a part of diverse tourism offer in rural settings (Demirović et al 2017;Mijatov et al, 2018). Serbian cuisine is characterized by highly diverse, strong and spicy food, which can be approximately described as a mixture of Turkish, Greek, Bulgarian, German and Hungarian cuisines.…”
Section: Introductionmentioning
confidence: 99%